Smart Technology Trends in Industrial and Business Management - Cagáňová, Dagmar; Balog, Michal; Knapčíková, Lucia; Soviar, Jakub; Mezarcıöz, Serkan (EAI/Springer Innovations in Communication and Computing, 2019)
This book presents current developments in smart city research and application regarding the management of manufacturing systems, Industry 4.0, transportation, and business management. It suggests approaches to incorporating smart city innovations into manufacturing systems, with an eye towards competitiveness in a global environment. The same pro-innovative approach is then applied to business and cooperation management. The authors also present smart city transportation solutions including vehicle data processing/reporting system, mobile application for fleet managers, bus drivers, bus passengers and special applications for smart city buses like passenger counting system, IP cameras, GPS system etc. The goal of the book is to establish channels of communication and disseminate knowledge among researchers and professionals working on smart city research and application. Features contributions on a variety of topics relatedto smart cities from global researchers and professionals in a wide range of sectors; Presents topics relating to smart cities such as manufacturing, business, and transportation; Includes expanded selected papers from EAI International Conference on Management of Manufacturing Systems (MMS 2016), EAI Industry of Things and Future Technologies Conference - Mobility IoT 2016 and International Conference on Smart Electric Vehicles and Vehicular Ad-hoc NETworks (SEVNET).